Cardiovascular and Stroke Risk in Japanese Hemodialysis Patients With Atrial Fibrillation. Issue 6 (29th November 2016) - Hasegawa, Jumpei; Bieber, Brian; Larkina, Maria; Robinson, Bruce M.; Wakai, Sachiko; Akizawa, Tadao; Saito, Akira; Fukuhara, Shunichi; Akiba, Takashi
Abstract: Atrial fibrillation is one of the most common arrhythmias in hemodialysis patients. We evaluated its clinical outcomes among hemodialysis patients with atrial fibrillation in Japan. Using data derived from the Japanese Dialysis Outcomes and Practice Patterns Study, we analyzed backgrounds and outcomes among hemodialysis patients with and without atrial fibrillation in Japan. Among 7002 hemodialysis patients, the prevalence of atrial fibrillation was 5.7% and the incidence was 0.2 per 100 patient‐years. Atrial fibrillation was independently associated with all‐cause mortality (hazard ratio, 1.32; 95% confidence interval, 1.02–1.71) and cardiovascular events (hazard ratio, 1.39; 95% confidence interval, 1.15–1.68), but not with stroke events (hazard ratio, 0.77; 95% confidence interval, 0.55–1.06) after adjustment for other variables. We conclude that patients with atrial fibrillation experienced higher mortality and more cardiovascular events than did patients without atrial fibrillation, although the risk of stroke was lower than expected.